Wear Analysis of gun barrel drill blade in 1.0503 steel drilling process in Milpro HG12 oil environment with addition of ultra-dispersive copper particles and copper oxides - Rychlik, Kazimierz; Senderowski, Cezary (Technical Sciences, 2020)
This paper presents structural solutions for guiding a single-sharp barrel drill blade during deep hole drilling, and it analyzes the structural and technological problems associated with two modes of inserting the drill into the processed material in the first stage of drilling – with the use of a pilot hole or a guide sleeve. The kinematics of the object-tool system (P-N) and other technological parameters affecting the execution of pilot holes under strictly defined conditions were analyzed during deep drilling with barrel drills in the FNE 40NC AVIA vertical numerical milling machine. Performance tests involving two types of cooling-lubricating agents, Milpro HG12 oil with and without the addition of ultra-dispersive copper particles and copper oxides (0.05 ÷ 0.6 µm) and Panther GP-1 additive (PWPH PantherOil Poland), applied in a 1:100 ratio, were described. The wear of the barrel drill blade along the entire drilling path (Lw = 8,000 mm) for 112 holes, and the geometric wear coefficient Kw of the drill bit were determined in 1.0503 steel with the use of EB80 drills made of K15 cemented carbide (WC 94%, Co 6%) with a diameter Dc = 8 mm. The results of wear tests were compared with the results of tribological tests involving cooling lubricants and 1.0503 steel with the chemical composition of K15 tungsten carbide. The abrasive wear of friction pair and the performance of the barrel drill blade during deep hole drilling were analyzed under identical conditions.